LOLAS-2: Redesign of an Optical Turbulence Profiler with High Altitude-resolution. (12th August 2016) - Avila, R.; Zúñiga, C. A.; Tapia-Rodríguez, J. J.; Sánchez, L. J.; Cruz-González, I.; Avilés, J. L.; Valdés-Hernández, O.; Carrasco, E.
Abstract: We present the development, tests, and first results of the second-generation LOLAS-2. This instrument constitutes a strongly improved version of the prototype LOLAS, which is aimed at the measurement of optical turbulence profiles close to the ground, with high altitude-resolution. The method is based on the generalized Scidar principle that consists of taking double-star scintillation images on a defocused pupil plane and calculating in real time the autocovariance of the scintillation. The main components are an open-truss 40-cm Ritchey–Chrétien telescope, a German-type equatorial mount, an electron-multiplying CCD camera, and a dedicated acquisition and real-time data-processing software. The new optical design of LOLAS-2 is significantly simplified compared to the prototype. The experiments carried out to test the permanence of the image within the useful zone of the detector and the stability of the telescope focus show that LOLAS-2 can function without the use of the autoguiding and autofocus algorithms that were developed for the prototype version. Optical turbulence profiles obtained with the new LOLAS have the best altitude-resolution ever achieved with Scidar-like techniques (6.3 m). The simplification of the optical layout and the improved mechanical properties of the telescope and mount make of LOLAS-2 a more robust instrument.